Lichens and lichenicolous fungi of the “Staroberdyans’ky” and “Altagirs’ky” forests (South Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
49 species of lichens and 3 species of lichenicolous fungi from 30 genera, 15 families and 5 orders are recorded in man-made forests of “Altagir” (46 species) and “Staroberdyansky” (37 species) in Melitopolskiy district (Zaporiz’ka oblast). 38 species are newly recorded for the Zaporiz’ka oblast.
Keywords: artificial woodlands, corticolous lichens, lichenicolous fungi, Zaporizha oblast, Melitopolsky region, Ukraine.